1993
DOI: 10.1007/bf00006186
|View full text |Cite
|
Sign up to set email alerts
|

Leaf dynamics and standing stocks of intertidal Zostera noltii Hornem. and Cymodocea nodosa (Ucria) Ascherson on the Banc d'Arguin (Mauritania)

Abstract: Leaf dynamics and standing stocks of intertidal seagrasses were studied in the Baie d'Aouatif (Parc National du Banc d'Arguin, Mauritania) in April and September 1988 . Standing stocks of Zostera noltii Hornem . suggest a unimodal seasonal curve similar to what is found for populations at higher latitudes . Also, leaf growth rates (0 .03 cm2 cm -2 day -1 on average) were similar to those found at higher latitudes in these months . Variation in leaf loss over tidal depth, time and different locations in the Bai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
2
5
0
1
Order By: Relevance
“…We measured CR both at night and during the day in opaque enclosures, and our estimates should be close to the daily averages. During our study, seagrass biomasses were similar to those previously reported for the Banc d'Arguin (van Lent et al 1991, Vermaat et al 1993, Honkoop et al 2008, Folmer et al 2012, with similar values in November and January.…”
Section: Validity Of Methods For Measuring Metabolismsupporting
confidence: 90%
See 2 more Smart Citations
“…We measured CR both at night and during the day in opaque enclosures, and our estimates should be close to the daily averages. During our study, seagrass biomasses were similar to those previously reported for the Banc d'Arguin (van Lent et al 1991, Vermaat et al 1993, Honkoop et al 2008, Folmer et al 2012, with similar values in November and January.…”
Section: Validity Of Methods For Measuring Metabolismsupporting
confidence: 90%
“…This significant winter production may be related to the dense periphyton cover observed in January, when damaged C. nodosa leaves were observed, which can compensate for less leaf photosynthesis in the winter (Enríquez et al 2004). The high CR in the subtidal areas may be due to the mineralization of organic matter produced locally (Holmer et al 2004) or imported from the intertidal zone, since Z. noltii leaf loss is greater than C. nodosa leaf loss in our study area (Vermaat et al 1993). This leaf loss led to hypoxia at the end of the night in the C. nodosa bed in November and probably during periods when the temperature was relatively high (August -October).…”
Section: Carbon Fluxes: Spatial and Temporal Variationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Z. noltii is frequently found in intertidal areas where it can be exposed to long periods of emersion and to strong tidal currents. Many studies have been conducted to measure the biomass, the growth and the production of Z. noltii in intertidal areas (Vermaat et al, 1987(Vermaat et al, , 1993Pérez-Lloréns and Niell, 1993;Philippart, 1995a;Auby and Labourg, 1996;Marbà et al, 1996;Vermaat and Verhagen, 1996;Brun et al, 2003). But few authors have attempted to compare Z. noltii biomass with the other components of the seagrass ecosystem (Asmus and Asmus, 1985;2000).…”
Section: Introductionmentioning
confidence: 99%
“…Το C. nodosa συναντάται επίσης σε ακτές του Ατλαντικού Ωκεανού, από την Πορτογαλία έως τη Σενεγάλη, ενώ είναι κοινό στα Κανάρια Νησιά (den Hartog, 1970, Short et al 2010. Κατανέμεται από τη μεσοπαραλιακή ζώνη μέχρι βάθους 33-35 m (Vermaat et al 1993, Reyes et al 1995, Canals & Ballesteros 1997, Short et al 2010) και μπορεί να βρεθεί σε ποικιλία κινητών υποστρωμάτων, από αδρή άμμο έως λασπώδη υποστρώματα (Peduzzi & Vukonič 1990, Pavón-Salas et al 2000. Αυτό το είδος μπορεί να αποικίσει διαφορετικούς περιβαλλοντικούς τύπους, όπως ανοικτά παράκτια ύδατα, εκβολές και λιμνοθάλασσες και σχηματίζει μονοειδικούς και, μερικές φορές, μικτούς λειμώνες με το Z. noltii (Terrados & Ros 1992, Cancemi et al 2002.…”
Section: τα θαλάσσια αγγειόσπερμα της μεσογείουunclassified